Mechatronic demonstrator for testing sensors to be used in mobile robotics functioning on the inverted pendulum concept. (August 2016) - Sandru, L; Dolga, V; Moldovan, C; Savu, D
Abstract: As the educational system is evolving, there are a lot of Mechatronic demonstrators used in schools and universities to demonstrate some technical, theoretical principle and analyzing new concept to apply this studied information, build practical hardware parts. The idea of using mobile robots for different applications is very common today. For choosing the best hardware and software configuration for the mobile robot it is necessary to make a documented analysis of the environment in which the mobile robot will perform. In our demonstrator we want to collect information from an optical sensor what can be used to maintain stability in a mobile robot equilibrium reading the reflected light from a surface. After hardware build we make a particularity study to see how optical sensors response in different ambient light and surface. To show some reference point we are collecting data from gyroscopic, accelerometer or rotation sensors.